2017
DOI: 10.1093/dote/dow035
|View full text |Cite
|
Sign up to set email alerts
|

Temporal patterns of hiatus hernia recurrence and hiatal failure: quality of life and recurrence after revision surgery

Abstract: Antireflux and paraesophageal hernia repair surgery is increasingly performed and there is an increased requirement for revision hiatus hernia surgery. There are no reports on the changes in types of failures and/or the variations in location of crural defects over time following primary surgery and limited reports on the outcomes of revision surgery. The aim of this study is to report the changes in types of hernia recurrence and location of crural defects following primary surgery, to test our hypothesis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 18 publications
1
14
0
1
Order By: Relevance
“…This study aims to address potential methodological problems by using two validated quality of life questionnaires (GERD-QOL and EQ-5D) to quantify the patient's recovery and allow for comparative analysis between intervention and standard procedure groups. We deliberately prioritise patient-reported outcomes (PROMs) above objective clinical measures, as the former are rightly the most important outcomes from hiatal hernia surgery [10]. A challenge of this, and previous RCTs, has been that powering it to detect reduction in symptomatic recurrence would require a sample size in excess of 1000 participants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study aims to address potential methodological problems by using two validated quality of life questionnaires (GERD-QOL and EQ-5D) to quantify the patient's recovery and allow for comparative analysis between intervention and standard procedure groups. We deliberately prioritise patient-reported outcomes (PROMs) above objective clinical measures, as the former are rightly the most important outcomes from hiatal hernia surgery [10]. A challenge of this, and previous RCTs, has been that powering it to detect reduction in symptomatic recurrence would require a sample size in excess of 1000 participants.…”
Section: Discussionmentioning
confidence: 99%
“…Hernia recurrence rates can be as high as 50% with standard suture repair, though this does include both small and large hernia recurrences. Revisional surgery for symptoms thought to be due to recurrence occurs This article is part of the Topical Collection on Surgery in approximately 5% of patients [10,11]. To mitigate this, some surgeons have tried modifications to the suture technique.…”
Section: Introductionmentioning
confidence: 99%
“…It tends to occur if the esophagus is not secured below the diaphragm. A modified cardiopexy has been described by some authors whereby the cardioesophageal junction and posterior wrap is secured to the median arcuate ligament [48]. Instead, the senior author of this paper performs a routine esophagopexy in addition to an anterior Dor fundoplication.…”
Section: Should Fundoplication Be Performed and Which One To Choose?mentioning
confidence: 99%
“…33 Consequently, it is not realistic to count merely on the mechanical and biological properties of the mesh for the long-term success of HH repair, but other factors such as release of axial tension through systematic mediastinal dissection and hernia sac excision should be considered to prevent HH recurrence. 34,35 Over the past decade, the use of the falciform ligament flap has been revisited as a onlay crural buttress to prevent or repair primary and recurrent HH. 36 We found that the vascular supply of the flap originating from the middle hepatic and inferior phrenic arteries is constant.…”
Section: Is Crura And/or Les Augmentation Needed?mentioning
confidence: 99%